Buddies: Tell Me How Much It Weighs - Shirley Willis (London, United Kingdom Hachette Children's Group, 1999)
In "Tell Me How Much It Weighs" the Buddies introduce the concept of weight by investigating the aspects involved. Units of weights, methods of measuring weights, and the importance of weight measurement for a variety of uses are explored.
Keywords: Read Aloud Non Fiction -- Read Aloud Non Fiction